Fentanyl withdrawal: Understanding symptom severity and exploring the role of body mass index on withdrawal symptoms and clearance. (13th December 2022) - Luba, Rachel; Jones, Jermaine; Choi, C. Jean; Comer, Sandra
Abstract: Background and Aims: Fentanyl is a highly lipophilic mu opioid receptor agonist, increasingly found in heroin and other drug supplies, that is contributing to marked increases in opioid‐related overdose and may be complicating treatment of opioid use disorder (OUD). This study aimed to measure the influence of body mass index (BMI) on fentanyl withdrawal and clearance. Design, Setting, Participants: This secondary analysis, from a 10‐day inpatient study on the safety and efficacy of sublingual dexmedetomidine for opioid withdrawal, includes participants with OUD ( n  = 150) recruited from three sites in New York, New Jersey and Florida, who were maintained on oral morphine (30 mg four times per day) for 5 days before starting study medication. Most participants ( n  = 118) tested positive for fentanyl on admission to the inpatient unit. Measurements: Urine toxicology and opioid withdrawal symptoms [Clinical Opioid Withdrawal Scale (COWS) and Short Opiate Withdrawal Scale (SOWS)] were assessed daily. The present analysis includes data on opioid withdrawal from days 1–5 of stabilization and urine toxicology data from days 1–10. Findings: Fentanyl status at admission was not significantly associated with COWS or SOWS scores after adjusting for sex, site and polysubstance use. Participants classified as overweight or obese ( n  = 66) had significantly higher odds of testing positive for fentanyl across days 1–10 [odds ratio (OR) = 1.65; P  < 0.01] and higher SOWS maximum scores across morphine stabilization ( P  < 0.05) compared to those with a healthy BMI ( n  = 68). Conclusions: Among inpatients with opioid use disorder, fentanyl status does not appear to be statistically significantly associated with Clinical Opioid Withdrawal Scale and Short Opiate Withdrawal Scale mean and maximum scores. High body mass index status (overweight or obese) appears to be an important predictor of slower fentanyl clearance and higher Short Opiate Withdrawal Scale maximum scores across the inpatient period than lower body mass index status.